Safety and feasibility of laparoscopic living donor right hepatectomy for adult liver transplantation: a meta-analysis. Issue 3 (March 2021) - Zhang, Wei; Xu, Lin; Zhang, Jianwei; Che, Xu
Abstract: Background: Laparoscopic living donor right hepatectomy (LDRH) was a controversial topic due to its unknown safety and feasibility. Methods: PubMed, EMBASE and Cochrane Library databases were searched for studies comparing LDRH with open living donor right hepatectomy (ODRH), which were published between the date of database establishment and June 2020. Revman5.3 was used for statistical analysis. Results: Fourteen studies were included. For the donors, there was no significant difference in warm ischemic time, hospital stay, graft weight, hepatic arterial anomalies (HAA), hepatic vein anomalies (HVA), portal vein anomalies (PVA), biliary anomalies, bleeding, wound infection, severe complication rate and readmission rate. The estimated blood loss, incidence of complication, intra-abdominal fluid rate in the LDRH group were significantly lower than those in the ODRH group, while the operation time, time to remove liver in the LDRH group were significantly higher than those in the ODRH group. For the recipients, there was no significant difference in complication rate, bleeding, HAA, PVA, biliary anomalies, graft failure and mortality. The HVA rate in the LDRH group was significantly higher than that in the ODRH group. Conclusion: LDRH is safe and feasible for adult living donor liver transplantation compared with ODRH and it can reduce intraoperative bleeding and postoperative complication in donors, which requires further verification by more multi-center comparative studies with large sample and high quality.